Mechanical Properties of Zirconia Materials with Different Translucency: An In Vitro Study - Rencber, Ayse; Karaman, Tahir (Quintessence Publishing Co Inc, 2024)
Purpose: To investigate the biaxial flexural strength of zirconia materials with different translucency before and after aging procedures and to evaluate the effects of aging on hardness and surface characteristics. Materials and Methods: A total of 90 disc-shaped specimens (n = 30 each) were prepared from translucent UTML, Kuraray Noritake) zirconia materials to a 016 x 1.2 mm thickness. The different translucency discs were then divided into three subgroups; one group was subjected to aging in a chewing simulator (n = 10), one group was aged with thermocycling (n = 10), and one was a control group (n = 10). Biaxial flexural strength, Vickers hardness, and surface characteristics were examined for all discs. The data were analyzed using the Shapiro-Wilk (P = .05), Mann-Whitney U, and Kruskal-Wallis H tests. Fracture strength was determined using biaxial bending strength tests, and Weibull analysis was used to analyze the resulting data. Results: A statistically significant difference was found among zirconia materials with different translucency in terms of fracture strength. On average, fracture strength was highest in the Upcera ST group (1,932.87 MPa) and lowest in the Katana UTML group (1,073.6 MPa; P= .001). The results of Weibull analysis showed a statistically similar distribution for all groups. Conclusions: Aging procedures did not cause significant differences in fracture strength and hardness. The fracture strength of the zirconia materials with different translucency was considered acceptable for intraoral use. Int J Prosthodont 2024;3772-79. doi: 10.11607/ijp.8164
Keywords: All-Ceramic Crowns; Flexural Strength; Fracture Strength; Reliability; Wear